Flood Disaster Mitigation Using the HEC-RAS Application to Determine River Water Levels in the Old City Area of Jakarta - Sejati, Wahyu; Paramitha AH, Dina; Khansa, Fathya; Maulana, Aryo Setyo; Julianingsih, Dwi (Pandawan, 2022)
The old city area is a tourist area strategically located in the heart of the capital city of DKI Jakarta. The Krukut river is one of the rivers that often overflow, which is one of the causes of flooding in Jakarta. This study aims to determine the water level of the Krukut river so that it can be used as a reference in handling flood disaster mitigation. This study uses the Nakayasu method and the Snyder method to calculate flood discharge, with a return period of up to 100 years. Meanwhile, for modeling the river water level using the HEC-RAS 5.0.07 application. The results of this study, specifically on the upstream cross-section until 300 meters after that TMA, are pretty high with plan one, which is 3 m deep from the bottom of the channel. However, the track still has a sufficient guard height of about 1.5 m. In other words, no overtopping/ river water does not overflow in the upstream area with a return period of 10 years and 25 years. However, due to the narrower channel section, the upstream region is more prone to flooding than the middle downstream area. From the modeling results, the channel prone to erosion is the section 10 track which is widening at the same time that the channel is not filled with the CONCRETE channel, so it is effortless to erode. For this reason, it is recommended to repair the walls of the river/channel to avoid scouring, especially if there is a high/extreme discharge.